The Influence of Teachers’ Work Motivation on Learning Community Activities at Junior High Schools in Sub-Rayon 04, Grobogan Regency - Sumastini Sumastini; Yovitha Yuliejantiningsih; Supriyono PS (Dinasti Publisher, 2025)
This study aims to analyze the effect of teachers’ work motivation on learning community activities at junior high schools in Sub Rayon 04, Grobogan Regency. The research employed a quantitative approach with a correlational design, involving a population of 215 teachers and a sample of 140 teachers selected using proportional random sampling. Data were collected through a closed-ended Likert-scale questionnaire and analyzed using simple linear regression with the assistance of SPSS for Windows version 28. The results showed that teachers’ work motivation was in the good category, indicating that most teachers had a positive drive in performing their duties. Statistical analysis revealed a very strong relationship between work motivation and learning community activities, with a correlation coefficient of 0.785 and a coefficient of determination of 0.564, meaning that 56.4% of the variation in learning community activities was influenced by work motivation, while 43.6% was affected by other factors beyond this study. The regression equation obtained was Ŷ = 31.133 + 0.781X, with a significance value of 0.000 < 0.05, indicating that work motivation has a positive and significant effect on learning community activities. High teacher motivation, whether stemming from internal factors such as responsibility, job satisfaction, and the desire to develop competencies, or from external factors such as principal support and a conducive work environment, has been proven to encourage greater teacher participation in learning communities. Teachers with strong motivation tend to be more active in sharing knowledge, engaging in discussions, and developing instructional innovations.